Responsibilities of The Land Deed Official (PPAT) Subject Installation of Encumbrance on Credit Guarantee in Deed Granting Process Mortgage (APHT) at Bank BPR Karya Remaja Indramayu District - Fikrina Setyo Rini; Agus Yuliana Indra; Amin Purnawan (Jurnal Akta, 2018)
The purpose of this study was to: 1) To determine responsibility regarding installation PPAT Encumbrance on credit guarantees in the process APHT on Bank BPR Karya Remaja Indramayu district. 2) To know the problems and solutions do just about anything regarding installation PPAT Encumbrance on credit guarantees in the process APHT in Bank BPR Karya Remaja Indramayu district. The data used in this study are primary data and analyzed with descriptive analytical method.Based on the results of data analysis concluded that: 1) PPAT responsible for making Deed Granting Mortgage in accordance with the provisions set forth in the legislation in force, in this case the Deed Granting Mortgage shall be in accordance with the occurrence, status, and data are correct, and supported by documents in accordance with the legislation. PPAT deed made by it must be made correctly in order to create a sense of security to the parties so that all can go smoothly and there are no losers. 2) Constraints in the installation APHT Mortgage in the process is that it lacks the completeness of the file, not a guarantee in the form of certificates, as well as the difference between self-identity in the name of National Identity Card with the name on the certificate. Therefore, the bank and PPAT should actively cooperate in completing the file completeness of the debtor and if the warranty is still in the process of making the certificate, then as a substitute for bank guarantees issued PPAT as partners covernote.Keywords: Responsibility PPAT; Credit agreement; Installation Mortgage.